Behavioral medicine and behavioral health research and practice: An introduction to the Special Issue. (April 2019) - Zvolensky, Michael J.; Smits, Jasper A.J.; Garey, Lorra
Abstract: The field of behavioral medicine continues to have a major impact on psychological science and public health. Presently, the field of behavioral medicine is undergoing rapid development and continues to evolve as a sub-discipline in allied disciplines. This Special Issue highlights emerging work that contributes to the evolution of behavioral medicine as pertaining to behavioral, psychosocial, and biomedical science integration to prevent, diagnose, and treat illness and disease. The present introductory article calls attention to research in behavioral medicine in the larger context of behavioral health research and practice and encourages continued research in this area. Research presented in this Special Issue covers a variety of topics, ranging from the role of cognition and emotion in behavioral disorders, development and refinement of novel technological and integrated interventions, substance use comorbidity, sexual health across special populations, and social determinants of health. This Special Issue is organized into three parts classified as transdiagnostic processes in health behavior and physical illness; personalization of health-specific therapeutic tactics in modern day healthcare in behavioral medicine; and social determinants of health and health disparities in behavioral medicine among special populations. It is hoped that this issue will alert readers to the significance of this work, illustrate the many domains currently being explored via innovative approaches, and identify promising and impactful areas for research.